Long-term Follow-up Results after Flow Diverter Therapy Using the Pipeline Embolization Device for Large or Giant Unruptured Internal Carotid Artery Aneurysms: Single-center Retrospective Analysis in the Japanese Population - OISHI, Hidenori; YATOMI, Kenji; FUJII, Takashi; MITOME-MISHIMA, Yumiko; TERANISHI, Kohsuke; SUZUKI, Kazumoto; KONDO, Akihide (Neurologia medico-chirurgica, 2022)
Flow diverter (FD) therapy using Pipeline embolization device (PED) has become an important alternative to treat internal carotid artery (ICA) aneurysms. Herein, we report the long-term outcome for 3 years after FD therapy using PED for ICA aneurysms in Japan. The patients who underwent angiographical and/or clinical follow-up for 3 years after the FD therapy using PED of large or giant unruptured ICA aneurysms from December 2012 at our university hospital are the subjects of this study. We retrospectively reviewed the in- and outpatients’ medical charts, and written operative and radiological records. There were 84 patients with 90 aneurysms who could be clinically and/or angiographically followed up for 3 years. Of these, 7 aneurysms were only available for clinical follow-up. Of the remaining 83 aneurysms, 6 aneurysms had vessel occlusion due to stent thrombosis or parent artery occlusion, and 60 of the remaining 77 (77.9%) had complete occlusion. In multivariate analysis, older age (>70 years), wide neck, and non-adjunctive coiling contributed statistically significantly to incomplete occlusion. Of the 84 patients, 2 patients (2.4%) had delayed complications between 6 months and 3 years after the initial FD placement. Three patients (3.6%) had poor outcome due to postoperative major stroke complications, 2 of which were acute complications. The long-term results after FD therapy are good both angiographically and clinically. Endothelialization of the aneurysmal neck and intra-aneurysmal thrombosis contribute to complete occlusion. The primary reason for the somewhat low complete occlusion in Japan may be the patients are generally older.